1999
DOI: 10.1118/1.598592
|View full text |Cite
|
Sign up to set email alerts
|

A novel 675.2 nm diode laser densitometer for use with GafChromic films

Abstract: In this article we compare the accuracy of a diode laser densitometer emitting 675.2 nm to that of a commercial He-Ne laser densitometer emitting 632.8 nm for GafChromic MD-55 film readout. A Leksell gamma unit (AB Elekta Stockholm, Sweden) Model B with a 14 and 8 mm collimator at the same isocenter (combined 11 mm collimator) was used to irradiate GafChromic MD-55 films. Dose response curves, dose cross profile and FWHM were measured with a custom-designed diode laser scanning device, emitting light at 675.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Light emitting diodes (LEDs) are available over a range of wavelengths from infra-red down to ultraviolet and have spectral bandwidths of approximately 30nm. A special subgroup of LEDs known as laser diodes are available at particular wavelengths and have narrower bandwidths than standard LEDs, at 1-10nm [67][68][69] FIGURE 10…”
Section: Typesmentioning
confidence: 99%
“…Light emitting diodes (LEDs) are available over a range of wavelengths from infra-red down to ultraviolet and have spectral bandwidths of approximately 30nm. A special subgroup of LEDs known as laser diodes are available at particular wavelengths and have narrower bandwidths than standard LEDs, at 1-10nm [67][68][69] FIGURE 10…”
Section: Typesmentioning
confidence: 99%
“…Several authors have discussed the dosimetry by using radiochromic films. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Niromand et al 16 reported on nearly all features and phenomena on GAFCHROMIC® films, McLaughlin 35 studied the response of these films and its use as a detector for radiosurgery 42 and Meigooni et al 10 reported on methods to improve the quality of the film dosimetry with radiochromic films. FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Radiochrome Filme sind nahezu gewebeäquivalent [23] und ihre Empfindlichkeit ist energieunabhängig [18]. Die Verfärbung der sensitiven Schicht des GAFCHROMIC™-Films durch Bestrahlung zeigt eine breite Absorptionsverteilung im Sichtbaren mit zwei Absorptionsmaxima bei 610 und 676 nm [9]. Der Film ist selbst entwickelnd, zeigt Additivität, hat eine exzellente Ortsauflösung und erlaubt absolute Dosismessungen.…”
Section: Komponenten Des Systems Detektorunclassified